Keistimewaan Guru dalam Perspektif Islam - Nurhasan Nurhasan (Jurnal Pendidikan Dirgantara, 2024)
Education plays a fundamental role as the primary foundation for shaping character, personality, and mastery of knowledge. From an Islamic perspective, the position of teachers is crucial, as they are not merely instructors but also serve as moral, spiritual, and social guides for students. This study aims to explain the uniqueness of teachers from an Islamic perspective by highlighting their status, role, and relevance in contemporary education. The research method employed is descriptive qualitative with a literature review, conducted through a review of relevant literature. The findings indicate that teachers are viewed as respected figures and agents of change responsible for instilling values ​​of faith, knowledge, and noble morals in future generations. However, current reality shows that respect for teachers is often declining, as this profession is often viewed as merely a formal job without considering the inherent noble values. Therefore, this study emphasizes the urgency of renewing public understanding regarding the uniqueness of teachers from an Islamic perspective, so that their strategic position and role are maintained. The recommendations from this study invite all elements, including society, students, and policy makers, to increase respect for teachers, while teachers themselves are expected to continue to improve their professional competence, provide real examples, and serve with full sincerity for the sake of realizing a generation that is intelligent, knowledgeable, faithful, and has good morals in accordance with Islamic guidance.